Perkembangan Ilmu Akuntansi di Era Modern : Kajian Epistemologi - Galih Mulya Subastyan; Sari Kartikaningrum; Miratul Husna Neris (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This article examines the development of accounting science in the modern era through an epistemological approach, focusing on the influence of globalization, economic dynamics, and rapid advances in information technology. A fundamental change occurred when the role of accounting shifted from merely recording transactions to becoming a strategic instrument that plays an important role in the business decision-making process. This shift indicates that accounting is no longer viewed as an administrative activity, but as an information system capable of providing added value to organizations. The integration of technologies such as accounting information systems, financial software, and big data analysis has brought about major changes in accounting practices, making them more efficient, accurate, transparent, and adaptive to the times. Through an epistemological review, a deep understanding of the origins, structure, and validity of accounting knowledge is obtained, including the philosophical dimensions that shape the framework of thinking and methodology in this discipline. Using a literature review method, this article emphasizes that the development of accounting is not only oriented towards technical aspects, but also towards conceptual and philosophical foundations that strengthen its position in facing modern business challenges. Accounting now plays an important role in supporting decision making, creating organizational efficiency, and responding to the needs of economic globalization.